2004
DOI: 10.1093/cesifo/50.3.541
|View full text |Cite
|
Sign up to set email alerts
|

Household Taxation, Income Splitting and Labor Supply Incentives - A Microsimulation Study for Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
78
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 8 publications
20
78
0
1
Order By: Relevance
“…While the hours elasticity for single men is in a comparable range, our estimates for (Steiner and Wrohlich, 2004;Peichl et al, 2010) or Belgium (Orsini, 2006), are in similar ranges. For further interpretation of these elasticities we present two additional sets of results.…”
Section: Estimation Resultssupporting
confidence: 64%
“…While the hours elasticity for single men is in a comparable range, our estimates for (Steiner and Wrohlich, 2004;Peichl et al, 2010) or Belgium (Orsini, 2006), are in similar ranges. For further interpretation of these elasticities we present two additional sets of results.…”
Section: Estimation Resultssupporting
confidence: 64%
“…In the case of parents of pre-school children joint employment involves often substantial childcare costs, which further contributes to the financial disincentives to work for the second earner. Research on the consequences of such features using data for other countries suggests that they play an important role in determining the pattern of employment among couples (Dearing et al, 2007;Steiner and Wrohlich, 2004).…”
Section: Figure 1 Herementioning
confidence: 99%
“…In fact, it has been shown that the relatively low labor force participation rate of married women in Germany is closely related to the negative labor supply incentives for secondary earners implied by the tax system (Steiner and Wrohlich 2004;see Dearing et al (2007) for a comparison between Germany and Austria, a countriy with individual income taxation. ).…”
Section: Introductionmentioning
confidence: 99%
“…Estimation results proved rather insensitive to realistic changes in the value chosen for this parameter. For example, changing the maximum number from 80 to 60 hours per week had very little effect on the estimation results 17 For a more detailed description and motivation of this model, see Steiner and Wrohlich (2004) referring to the non-linear terms, the vector β the corresponding coefficients of the linear terms. ε k is a stochastic error term accounting for factors affecting the household's utility other than leisure and income.…”
mentioning
confidence: 99%